Critical Financial Education: a training for trainers - Schneider, Tcharles (2018)
This article socializes the results of the Critical Financial Education theme proposed in the continuing education of the professionals of a public school. The relevance of this theme is justified by the complaints of a part of the servers with financial problems that directly influence their work as a teacher. The research, with a qualitative approach, used case study characteristics. Data collection took place through the recording of the training audios, which were later transcribed. We also used semi-open questionnaires that presented situations of everyday problems. The pedagogical intervention developed provided several moments of reflection on the financial practices that are adopted in the course of daily life. Regarding the use of credit cards and other credit lines, there was a simplistic conception of the use and function of the credit card, as well as the lack of knowledge of rates or financial charges. It was observed the need to implement mathematical concepts, in the most diverse situations, since the professionals who do not have training in the area of the Exact, requested help to solve mathematical problems of the daily life. It can be inferred that this pedagogical intervention with the professionals of the education contributed to subsidize relevant aspects to be addressed in the activities proposed to high school students.